Critical Approaches for Nursing Research: Queer Research Methods - Ahtisham Younas (Creative Nursing, 2026)
In Creative Nursing Volume 32, we introduced a new series on Critical Approaches for Nursing Research. The primary purpose of this series is to help nurse researchers understand, design, and conduct research that is necessary for dismantling structural inequalities in healthcare. Critical research is pertinent to unraveling the sociohistorical context and nature of knowledge, and how generated knowledge can bring about disruptive change in society. This final editorial in the series offers an overview of queer research methods.